The Combination Effect of Vitamin C and E on the Number of Hemoglobin, Leukocyte and Platelet Post-Irradiation of Gamma Ray - Roni Prisyanto; Didik R Santoso; Unggul P Juswono; Yeni Cahyati (Natural B, Journal of Health and Environmental Sciences, 2014)
Radiotherapy is an alternative treatment for cancer patients to inhibit and destroy cancer cells due to the ionization. Gamma rays ionize not only cancer cells but also damage healthy cells due to precence of free radicals produced by ionizing gamma rays when interacting with biological material. The decrease in blood cells as ie hemoglobin, leukocytes and platelets caused free radicals can be minimized by administering antioxidant vitamins C and E. This study was conducted to determine the effects of gamma radiation exposure to the decrease in hemoglobin blood cells, leukocytes and platelets of mice after administration of a combination of antioxidant vitamins C and E in five variations, namely 10 mg dose: 1μl, 15 mg: 1.5 μl, 20 mg: 2 μl, 25 mg: 2.5 μl, 30 mg: 3 μl. Exposure of gamma radiation was given fractionation ranging from 200 rads to 1000 rads. Blood was taken from the heart for hemoglobin, leukocytes and platelets tests. The results showed that the administration of vitamins C and E may reduce the decline in hemoglobin levels, leukocytes, platelets resulting from exposure to gamma radiation when compared to the control group or without vitamin.